(untitled) (Sound Stage Screen, 2021)
The philosophical and general cultural contribution of Philip Auslander’s work to music, media, and the arts considered as performance is the radical, critical, and self-critical questioning of cultural dichotomies that often trap our thoughts exactly when they seem to help us think more clearly. Intervewed by Alessandro Cecchi, Auslander reflects on the exploration of the “continuum” between sound and vision, technique and technology, performance and media, music and the arts considered in their continuously and mutually changing relationships. Philip Auslander is a Professor of Performance Studies and Popular Musicology in the School of Literature, Media, and Communication of the Georgia Institute of Technology (Atlanta, Georgia, USA). He is the author of numerous scholarly articles and seven books, including Presence and Resistance: Postmodernism and Cultural Politics in Contemporary American Performance (University of Michigan Press, 1992), From Acting to Performance: Essays in Modernism and Postmodernism (Routledge, 1997), Liveness: Performance in a Mediatized Culture (Routledge, 1999; 2nd ed. 2008),Performing Glam Rock: Gender and Theatricality in Popular Music (University of Michigan Press, 2006), Reactivations: Essays on Performance and Its Documentation (University of Michigan Press, 2018), and In Concert: Performing Musical Persona (University of Michigan Press, 2021). In addition to his scholarly work on performance and music, Prof. Auslander has written art criticism for ArtForum and other publications and regularly contributes essays to exhibition catalogs for museums in Europe and North America, including Tate Modern, The Whitney Museum of American Art, the Migros Museum, and the Walker Art Center. He is also a screen actor and writer. “Dr. Blues,” a short film Auslander wrote, produced, and acted in, premiered at the Peachtree Village International Film Festival in Atlanta in October of 2019.